The thioredoxin system determines CHK1 inhibitor sensitivity via redox-mediated regulation of ribonucleotide reductase activity - Prasad, Chandra Bhushan; Oo, Adrian; Liu, Yujie; Qiu, Zhaojun; Zhong, Yaogang; Li, Na; Singh, Deepika; Xin, Xiwen; Cho, Young-Jae; Li, Zaibo; Zhang, Xiaoli; Yan, Chunhong; et al. (Nature communications, 2024)
Checkpoint kinase 1 (CHK1) is critical for cell survival under replication stress (RS). CHK1 inhibitors (CHK1i’s) in combination with chemotherapy have shown promising results in preclinical studies but have displayed minimal efficacy with substantial toxicity in clinical trials. To explore combinatorial strategies that can overcome these limitations, we perform an unbiased high-throughput screen in a non-small cell lung cancer (NSCLC) cell line and identify thioredoxin1 (Trx1), a major component of the mammalian antioxidant-system, as a determinant of CHK1i sensitivity. We establish a role for redox recycling of RRM1, the larger subunit of ribonucleotide reductase (RNR), and a depletion of the deoxynucleotide pool in this Trx1-mediated CHK1i sensitivity. Further, the TrxR inhibitor auranofin, an approved anti-rheumatoid arthritis drug, shows a synergistic interaction with CHK1i via interruption of the deoxynucleotide pool. Together, we show a pharmacological combination to treat NSCLC that relies on a redox regulatory link between the Trx system and mammalian RNR activity. The clinical application of inhibitors targeting checkpoint kinase 1 (CHK1) is challenged by limited efficacy. Here, the authors identify that thioredoxin (Trx) system inhibition mediates sensitivity to CHK1 inhibitor via regulating the activity of ribonucleotide reductase, demonstrating the synergistic effect of CHK1 inhibitor and inhibitors targeting Trx system in lung cancer models.